(untitled) (International Journal of Physiotherapy, 2025)
Background: Air rifle shooting is a precision sport requiring stability, muscle endurance, and fine motor control. Hand grip strength and shoulder muscle stability are critical for accuracy and consistency. Limited research has examined the direct impact of strength training on shooting performance. This study aimed to evaluate the impact of a hand-grip and shoulder muscle-strengthening programme on the performance of air rifle shooters. Methods: A pre- & post-experimental study was conducted with 15 air rifle shooters (aged 11–17 years) in the Mangalore Rifle club. Participants underwent a six-week strength training intervention using hand grippers, therabands, and therapeutic putty. Pre- and post-intervention analyses included hand grip strength, shoulder muscle strength (measured with a handheld dynamometer), and shooting performance (scored out of 600 points according to ISSF guidelines). Statistical analysis performed used paired t-tests (p < 0.05). Results: Significant improvements (p = 0.001) were observed in hand grip strength (15.33% right, 16.47% left), shoulder flexors (19.33% right, 15.24% left), abductors (19.96% right, 17.80% left), external rotators (20.34% right, 23.01% left), and internal rotators (22.56% right, 22.22% left). Shooting performance increased 7.14%, from a mean score of 511.53 to 548.07 out of 600 points (p = 0.001), reflecting statistically significant improvement and reduced variability. Conclusion: Targeted hand grip and shoulder muscle strength training significantly enhance shooting performance in air rifle shooters. Strengthening programs focused on hand grip and shoulder stability should be integrated into training regimens to optimize shooting accuracy and consistency.